2004
DOI: 10.4049/jimmunol.173.2.818
|View full text |Cite
|
Sign up to set email alerts
|

Decreased E47 in Senescent B Cell Precursors Is Stage Specific and Regulated Posttranslationally by Protein Turnover

Abstract: The E2A-encoded transcription factor E47 is crucial to B lymphopoiesis. Senescent BALB/c mice (∼2 years old) had reduced pre-B cells ex vivo. Pro-B/early pre-B cells from these aged mice, both ex vivo and in vitro, were deficient in E47 protein. In vitro, IL-7 expanded pro-B/early pre-B cells from young BALB/c mice expressed E47 protein that was relatively stable over a 5-h period. Cultured senescent pro-B/early pre-B cells exhibited reduced E47 protein stability with ∼50–90% loss of E47 over the same time per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 55 publications
(121 reference statements)
4
83
0
Order By: Relevance
“…Turnover of the E2A proteins is governed by the ubiquitin-proteasome pathway. Previous studies, mostly focused on E2A protein regulation and degradation during B-cell development, have suggested that ubiquitin-proteasome mediated E2A protein degradation is one of the important mechanisms involved in the regulation of their cellular abundance and biological activities (Nie et al, 2003;Van der Put et al, 2004;Riley et al, 2005). However, little information is available regarding the regulation and degradation of the E2A proteins during muscle differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Turnover of the E2A proteins is governed by the ubiquitin-proteasome pathway. Previous studies, mostly focused on E2A protein regulation and degradation during B-cell development, have suggested that ubiquitin-proteasome mediated E2A protein degradation is one of the important mechanisms involved in the regulation of their cellular abundance and biological activities (Nie et al, 2003;Van der Put et al, 2004;Riley et al, 2005). However, little information is available regarding the regulation and degradation of the E2A proteins during muscle differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Densitometry values for desired proteins were normalized to that of the loading controls. In some experiments, normalized values of experimental proteins in old lysates (e.g., E47) were expressed relative to young controls (9,12).…”
Section: Immunoprecipitation and Western Blot Analysismentioning
confidence: 99%
“…Both transcription of the RAG enzymes and the surrogate L chain proteins in B cell precursors are, in part, mediated by the E2A-encoded transcription factors E47 and E12 (10). Previously, we have shown that E2A-encoded protein levels are reduced in B cell precursors from aged mice after their expansion with IL-7 in vitro (9,11,12). This was associated with reduction in the expression of 5 protein and reflected in decreased 5 and VpreB mRNAs (9).…”
mentioning
confidence: 95%
See 2 more Smart Citations